Optimization of ACO-GA for Routing Optimization - Vajpayee, AK; Faisal, SM (International Journal of Computer Sciences and Engineering, 2025)
For network routing optimization many protocols and methods are evolved over time and this continuous race for more accurate and speedy data delivery is going on, our research is also one attempt on that race. Nature is best knowledge available on this planet, so ignoring this available science on any field would be foolish. Ants are social insects that searches food collectively and passed their knowledge of food path to others by leaving a hormone called pheromone on the way; researches used this earlier solely and with Genetics for routing optimization. Combination of both is used in routing optimization where output of GA is passed on ACO algorithm but we proposed to use firstly ACO and then passed the output of ACO in GA to get possible path. By our approach we not only reduced the domain of routes for GA but also optimized the time, every time GA uses for evolving best set of chromosomes. We just not only optimized the routing but also optimized earlier research of combination of ACO and GA.